Approaches to investigate the role of chelation in the corrosivity of biomass-derived oils. (February 2020) - Connatser, Raynella M.; Frith, Matthew G.; Jun, Jiheon; Lewis, Samuel A.; Brady, Michael P.; Keiser, James R.
Abstract: The need to provide the U.S. market with a renewable liquid fuel energy source from a non-food feedstock stream has gained considerable traction due to benefits such as improved energy efficiency, reduced environmental impacts, and enhanced national security. Practical achievement of these goals via biomass and bio-waste utilization involves production of liquid intermediates containing corrosive, reactive species like carboxylic acids, ketones, aldehydes, and hydroxyaldehydes. Such mixtures challenge materials of containment, processing, and transport. It is widely recognized that the smaller organic acids, such as acetic and formic, are corrosive and can remove protective surface oxides on alloys used in bio-oil processing infrastructure, and ketones can swell sealing polymers. However, literature shows, and findings herein confirm, larger carboxylic acids and bidentate alcohols are present. This highlights the potential for synergistic, detrimental effects of constituents in bio-oil corrosion, including direct reactivity of small acids compounded with the possibility of mobilization of protective metal oxide layers via chelation by larger acids and oxygenates. The question of whether species beyond small acids can significantly contribute to corrosion requires analytical approaches previously not applied to bio-oil corrosion studies and certainly not previously applied corroboratively. This work introduces a combination of optical, mass spectral, and electrochemical impedance spectroscopies with an incubation approach to study metal mobilization, to facilitate elucidating chelation's role in bio-oil corrosive pathways. To enable systematic study of these oxygenates' material compatibility individually and in combination, a model matrix of bio-oil constituents was also developed based on identification of key components of real bio-oils. Highlights: Optical & electrochemical impedance spectroscopies combined with alloy leaching. Advanced mass spectrometry confirms multi-oxygenated acids in fast pyrolysis oil. Raman confirms persistence of multi-oxygenates on industrial alloy surface. New electrochemical impedence geometry implemented for multi-oxygenate response. Alloy incubation/leach method indicates bio-oil constituents' corrosivity trends.